2020
DOI: 10.3390/rs12111814
|View full text |Cite
|
Sign up to set email alerts
|

Using Multi-Temporal MODIS NDVI Data to Monitor Tea Status and Forecast Yield: A Case Study at Tanuyen, Laichau, Vietnam

Abstract: Tea is a cash crop that improves the quality of life for people in the Tanuyen District of Laichau Province, Vietnam. Tea yield, however, has stagnated in recent years, due to changes in temperature, precipitation, the age of the tea bushes, and diseases. Developing an approach for monitoring tea bushes by remote sensing and Geographic Information Systems (GIS) might be a way to alleviate this problem. Using multi-temporal remote sensing data, the paper details an investigation of the changes in tea health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The visible reflectance bands can be splitted into three main regions, red (650–700 nm), green (495–570 nm), and violet–blue (390–495 nm) ( Hennessy et al, 2020 ). Most studies were emphasized the importance of red spectral bands or the combined use of red and red edge bands as one solid index in predicting the total yield ( Jolly et al, 2005 ; Filippa et al, 2018 ; Lykhovyd, 2020 ; Phan et al, 2020 ; Tiwari and Shukla, 2020 ). In this study, we identified highly ranked bands in the violet and red regions for classifying the soybean seed yield, centered at 395 nm, 665 nm, and 675 nm ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The visible reflectance bands can be splitted into three main regions, red (650–700 nm), green (495–570 nm), and violet–blue (390–495 nm) ( Hennessy et al, 2020 ). Most studies were emphasized the importance of red spectral bands or the combined use of red and red edge bands as one solid index in predicting the total yield ( Jolly et al, 2005 ; Filippa et al, 2018 ; Lykhovyd, 2020 ; Phan et al, 2020 ; Tiwari and Shukla, 2020 ). In this study, we identified highly ranked bands in the violet and red regions for classifying the soybean seed yield, centered at 395 nm, 665 nm, and 675 nm ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned biophysical and biochemical attributes are strongly connected to the overall health conditions of vegetation (Marandi et al 2021;Phan et al 2020), including tea plantations and productivity. However, other environmental variables (rainfall, temperature, relative humidity, solar radiation, and soil moisture), extreme weather conditions (i.e., drought, floods, and heatwaves), and climate variability (e.g., ENSO) also determine the productivity of tea (Ahmed et al 2014;Raj et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…West Bengal produces tea mainly from Darjeeling, Dooars (Jalpaiguri), and Terai (North Dinajpur) regions, contributing nearly 24% of the total production of India (Tea Board of India 2018). Tea usually does not compete with food crops and hence, tea plantations are mostly found over bare land and bare hills (Phan et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…where R xy is the Pearson correlation coefficients for x and y variable which have value from −1 to 1. x i is NDVI value in the ith month [38], y i is the mean monthly climate factor in the ith month [24] and x y are the average of x and y, respectively.…”
Section: Analysis Of Relationship Between Ndvi and Meteorological Parametersmentioning
confidence: 99%
“…From a large number of individual trees generated, they voted the most popular classes. Many research showed that RF may reach the best predictive performances compared to other methodologies [38,45,46].…”
Section: Support Vector Machine and Random Forest For Estimating Tea Yieldmentioning
confidence: 99%